The covert mechanisms of education policy discourse: Unmasking policy insiders' discourses and discursive strategies in upholding or challenging racism and classism in education - Melanie Bertrand; Wendy Y. Perez; John Rogers (Arizona State University, 2015)
Policy insiders across party lines increasingly acknowledge educational "gaps," yet they talk about this inequity in very different ways. Though some critique disparities through a structural lens, others use deficit discourse, blaming families of color and working-class families for educational outcomes. This study examines how state policy insiders explain educational inequity, shedding light on the complex relationship between language and the maintenance of systemic racism and classism in education. Drawing upon a unique data set of interviews with 50 policy insiders in one state in the United States, we found three main discourses used to explain inequity in education, each of which cited a different cause: 1) structural inequity, 2) perceived deficits of families and communities, and 3) teachers unions and teacher seniority. Policy insiders used often-veiled discursive strategies to advance their discourses. For instance, those that used deficit discourse: 1) asserted that those most negatively impacted by inequity cause inequity; 2) strengthened deficit discourse by blending it with one or both of the other two discourses; and 3) made inequity appear natural through the use of several substrategies, including obscuring the identity of those harmed by inequity. These strategies allowed some policy insiders to strengthen deficit discourse, divert attention from structural issues, and characterize themselves positively while advancing racist and classist ideas. These findings have compelling implications in terms of possibilities for policy changes supportive of educational equity.